Larangan Berjualan Di Badan Jalan Umum - Mikrad Hidayat; Dermina Dalimunthe (IAIN Padangsidimpuan, 2022)
Based on the above background, the purpose of this study is to determine the implementation of the Padangsidimpuan City Regional Regulation Number 41 of 2003 Article 9 concerning the Prohibition of Selling on Public Roads. This research is motivated because there are lots of traders who sell who occupy places that have been determined by the Regional Government, but there are also traders who sell not in the right place or traders who sell in places that can disturb the community or other road users such as in sidewalk.The type of research used by the researcher is a qualitative research that is normative and empirical. the data used are primary and secondary data, data collection methods by observation, interviews and documents. The data collected were analyzed using editing, verification and analysis methods.Based on the results of the research above, it is obtained that the implementation of Regional Regulation Number 41 of 2003 Article 9 concerning the Prohibition of Selling on Public Road Agencies in Padangsidimpuan City has been running but not yet ideal. The Civil Service Police Unit has carried out raids, given warnings, provided sanctions in accordance with Article 9, but in the process of socializing and supervising street vendors who are still selling on Jalan Thamrin, it is not yet fully ideal, this can be seen by the number of street vendors selling on the street. Padangsidimpuan City Public Road Agency. And as for the obstacles/obstacles in this implementation: the lack of socialization of the Civil Service Police Unit to street vendors in the Public Road Agency, the lack of mindset of the street vendors in Padangsidimpuan City, and the lack of communication between the community and the Government. Judging from Fiqh Siyasah, that is actually the content of Regional Regulation Number 41 of 2003 Article 9 concerning the Prohibition of Selling in the Padangsidimpuan City Public Road Agency. Made for the benefit of the people, especially the public transport parties who do not feel the congestion anymore, pedestrians get comfort and space to walk comfortably